Outdoor versus indoor cultivation: Effects on the metabolite profile of Agaricus subrufescens strains analyzed by untargeted metabolomics - de Oliveira Gorgulho Silva, Caio; Raisa Barbosa Cunha, Joice; Almeida Conceição, Aparecido; Gonzaga Almeida, Euziclei; Cunha Zied, Diego [UNESP]; Gonçalves Vieira Junior, Wagner [UNESP]; Souza Dias, Eustáquio; Isikhuemhen, Omoanghe S.; Verardi Abdelnur, Patrícia; Gonçalves de Siqueira, Félix (Elsevier, 2022)
Agaricus subrufescens has emerged as an important culinary-medicinal mushroom over the last decades. Efforts have been dedicated to upgrade the A. subrufescens productive process via strain selection and cultivation scaling-up. However, little is known on the influence of those variables on the metabolite profiles and nutraceutical properties of this mushroom. In this work, the effects of outdoor versus indoor cultivation on the metabolite profiles of five commercial strains of A. subrufescens were investigated by untargeted metabolomics. UHPLC-MS coupled to multivariate data analysis revealed that the concentration of several metabolites with reported health-related properties as well as related to taste and browning varied significantly between strains and were affected by the cultivation system in a strain-dependent manner. Data suggest that increasing the production scale by means of indoor cultivation may decrease the nutraceutical quality of some A. subrufescens strains while also affecting taste and browning susceptibility to different extents.
Keywords: Bioactive metabolites; Cultivation method; Mass spectrometry; Medicinal mushroom; Untargeted metabolomics